2014
DOI: 10.1093/ndt/gfu013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of everolimus on renal angiomyolipoma in patients with tuberous sclerosis complex being treated for subependymal giant cell astrocytoma: subgroup results from the randomized, placebo-controlled, Phase 3 trial EXIST-1

Abstract: Everolimus showed efficacy in reducing angiomyolipoma lesion volume in patients with SEGA associated with TSC.The trial is registered with ClinicalTrials.gov, number NCT00789828; http://clinicaltrials.gov/ct2/show/NCT00789828?term=EXIST-1&rank=1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 17 publications
3
53
1
1
Order By: Relevance
“…The striking adverse effects in this case involve stomatitis, nasopharyngitis, and acne-like skin lesions (50). In another trial on TSC AML in patients with subependymal giant cell astrocytoma (SEGA), everolimus caused a decline of more than 50% in the tumor volume (51). Both these studies confirmed the efficiency and safety of everolimus (50,51).…”
Section: Treatmentsupporting
confidence: 53%
See 1 more Smart Citation
“…The striking adverse effects in this case involve stomatitis, nasopharyngitis, and acne-like skin lesions (50). In another trial on TSC AML in patients with subependymal giant cell astrocytoma (SEGA), everolimus caused a decline of more than 50% in the tumor volume (51). Both these studies confirmed the efficiency and safety of everolimus (50,51).…”
Section: Treatmentsupporting
confidence: 53%
“…In another trial on TSC AML in patients with subependymal giant cell astrocytoma (SEGA), everolimus caused a decline of more than 50% in the tumor volume (51). Both these studies confirmed the efficiency and safety of everolimus (50,51). All in all, according to the international TSC consensus group, recent recommendations for the treatment of AML patients with TSC, particularly in case of acute hemorrhage, include embolization and corticosteroids; as for asymptomatic lesions with a size larger than 3 cm, the administration of mTOR inhibitors followed by selective arterial emobilization or partial resection is recommended (36).…”
Section: Treatmentmentioning
confidence: 99%
“…The first mTOR inhibitor tried was sirolimus, also known as rapamycin, initially developed as an immunosuppressive agent in solid organ transplantations. Everolimus is a rapamycin derivative that has been recently studied with data from two randomized controlled trials suggesting safety and efficacy (72,73). EXIST-2, a double-blind-randomized controlled trial that included 118 patients with 3 cm or larger AMLs in the setting of TSC, randomized everolimus and placebo (67).…”
Section: Discussionmentioning
confidence: 99%
“…Angiomyolipoma volume reductions with everolimus were sustained over 48 weeks of treatment (fig. 2) [20]. In EXIST-2, the primary end point of angiomyolipoma response was achieved in 42% of patients (33 of 79) compared with 0% for placebo (0 of 39, p < 0.0001) after a median everolimus exposure of 8.7 months, and the median time to reach an angiomyolipoma response was 2.9 months [18].…”
Section: Outcome Of Interventionmentioning
confidence: 99%